2013
DOI: 10.1111/zph.12082
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Primary Care Physicians in the Franche‐Comte Region (France) Regarding the Risk of Rabies

Abstract: Impacts• Primary care physicians (PCPs) have some knowledge of the basic information about the risk of rabies (type of animal transmitting the disease, severity criteria for bites).• PCPs are not familiar with the indications for the rabies vaccine and rabies immunoglobulin.• PCPs' knowledge of how to manage and prevent rabies exposure often requires updating. SummaryRabies remains a public health concern and is associated with a mortality rate of nearly 100%. An observational survey was undertaken in 2010 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Before the present study, two surveys investigating the level of knowledge of rabies (Jeanpetit 2014) and travel medicine (Piotte 2013) were performed in the same geographical areas. For each survey, anonymous questionnaires were sent to physicians by post and the response rate was similar (35.5% for PCPs in the present study, 37.5% for the rabies survey and 38.5% for the travel medicine one).…”
Section: Discussionmentioning
confidence: 99%
“…Before the present study, two surveys investigating the level of knowledge of rabies (Jeanpetit 2014) and travel medicine (Piotte 2013) were performed in the same geographical areas. For each survey, anonymous questionnaires were sent to physicians by post and the response rate was similar (35.5% for PCPs in the present study, 37.5% for the rabies survey and 38.5% for the travel medicine one).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in a low rabies-risk area in Massachusetts, USA highlighted how large amounts of rabies PEP could be wasted in patients with low or non-existent risk of rabies exposure [23]. Studies in countries free of rabies [24] and in endemic areas [25][26][27] similarly reported insufficient rabies risk assessment due to clinicians' lack of familiarity with the recommendations, highlighting the need to update clinicians' knowledge [14]. Discordant rabies risk assessment and PEP practice was also apparent in our study.…”
mentioning
confidence: 99%
“…Other studies on clinician’s knowledge and attitudes, conducted in the USA (Florida, Kentucky), showed an unsatisfactorily low level of compliance with national guidelines resulting in inappropriate PEP treatment [17-19]. Studies in countries free of rabies [20] or in endemic areas [21-23] similarly reported insufficient rabies risk assessment due to a lack of familiarity of clinicians with the recommendations, and highlighted the need for knowledge updating [14]. Lack of agreement between rabies risk assessment by clinicians and the guidelines was also apparent in our study, although only a low percentage resulted in subsequent inappropriate prescription.…”
Section: Discussionmentioning
confidence: 99%